Challenges Students with Special Education in the Implementation of Teaching and Facilitation of Mathematics - Azmi, Nur Liyana; Tahar, Mohd. Mokhtar (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Students with special needs often associated with learning difficulties in subject of mathematics. Hence, this study aims to identify the challenges that arise in the implementation of teaching and facilitation of Mathematics for students with special educational needs in the Integrated Special Education Program. This concept paper is based on research in the library, which is through the collection of related information and materials to identify challenges that affect the implementation and facilitation in Mathematics as to increase the interest and performance of students with special needs towards Mathematics subjects. This concept paper is expected to help special education teachers in their efforts to diversify teaching methods that are capable of overcoming the challenges that arise in the implementation and facilitation in Mathematics subjects .The challenges which arise are regards to the special education teacher's delivery techniques, special need students factor itself which limits the learning of Mathematics to only take place in schools, the less attractive approaches and teaching method factor, and the limited use of teaching aids. Suggested implementation to increase special need students interest and performance in Mathematics subjects are the implementation of simulation, the implementation of pretend play, the implementation of student-centered teaching method, and the implementation of 21st Century Learning (PAK21).